Charge Recombination in Organic Photovoltaic Devices with High Open-Circuit Voltages - Westenhoff, Sebastian; Howard, Ian A; Hodgkiss, Justin M; Kirov, Kiril R; Bronstein, Hugo A; Williams, Charlotte K; Greenham, Neil C; Friend, Richard H (Journal of the American Chemical Society, 2008)
A detailed charge recombination mechanism is presented for organic photovoltaic devices with a high open-circuit voltage. In a binary blend comprised of polyfluorene copolymers, the performance-limiting process is found to be the efficient recombination of tightly bound charge pairs into neutral triplet excitons. We arrive at this conclusion using optical transient absorption (TA) spectroscopy with visible and IR probes and over seven decades of time resolution. By resolving the polarization of the TA signal, we track the movement of polaronic states generated at the heterojunction not only in time but also in space. It is found that the photogenerated charge pairs are remarkably immobile at the heterojunction during their lifetime. The charge pairs are shown to be subject to efficient intersystem crossing and terminally recombine into F8BT triplet excitons within ∼40 ns. Long-range charge separation competes rather unfavorably with intersystem crossing − 75% of all charge pairs decay into triplet excitons. Triplet exciton states are thermodynamically accessible in polymer solar cells with high open circuit voltage, and we therefore suggest this loss mechanism to be general. We discuss guidelines for the design of the next generation of organic photovoltaic materials where separating the metastable interfacial charge pairs within ∼40 ns is paramount.